Erosive pustular dermatosis of the scalp - is it really a rare condition? - Levakov Olivera; Gajić Branislava (Vojnosanitetski Pregled)
Introduction. Erosive pustular dermatosis of the scalp (EPDS) is a rare disorder of unknown etiology that usually occurs in the elderly and is characterized by multiple pustules, erosions and crusts that appear on the scalp leading to scarring alopecia. The histopathology and laboratory tests are not specific which is the reason that EPDS is a frequently misdiagnosed condition. Case report. We presented two patients with EPDS. The first patient had the known history of local trauma, both patients had chronic recidivant process, classic clinical presentations, and nonspecific histological findings. Each patient had prompt therapeutical response to potent topical steroids. Conclusion. The diagnosis of EPDS can be made if a condition fulfills the following criteria: atrophic or actinic damaged skin, clinical association of erosions, pustules, scales and crusts, no specific histopathology, no infectious agent found responsible for the condition, and chronic course leading to scarring alopecia, and prompt response to the treatment with topical steroids. The history of chemical or physical trauma is often present.